Persepsi Masyarakat Terhadap Nilai-Nilai Adat Dalam Melestarikan Lingkungan Hidup Di Desa Wombo Induk Kabupaten Donggala - Triwulan; Kapile, Charles (Jurusan Pendidikan IPS, Fakultas Keguruan dan Ilmu Pendidikan Universitas Tadulako, 2024)
The purpose of this study is to describe the values ​​of the community's customs and environmental preservation in Wombo Induk Village. This type of research is qualitative research with a descriptive approach. The informants consisted of village heads, traditional leaders, and the community. The types of data to be used in this study used primary data and secondary data. The data analysis technique has three steps, namely: data reduction, data display, and conclusion. The results of this study are: 1) people's understanding of environmental preservation is the process of protecting or protecting the environment from damage. Protecting the environment will have a positive impact on people's lives and if the environment around us is damaged it will have a negative impact on humans themselves. 2) the environment is not only seen as a provider of natural resources and as a life-supporting capacity that must be exploited, but also as a place to live which requires harmony and balance between humans and the environment. 3) the relationship between perceptions of traditional values ​​in preserving the environment. This is influenced by the moral values ​​or beliefs held by the local community. So that someone will judge or indirectly, someone will judge or perceive something that is right or wrong, important or not important. Wombo Induk Village itself has a normative attitude, concrete values ​​that are very visible, moral values ​​that are owned by every human being, and cultural values ​​that are still maintained.